Biologicals for the prevention of anaphylaxis. Issue 3 (June 2021) - Tanno, Luciana Kase; Demoly, Pascal
Abstract : Purpose of review: To review the use of biological agents (BA) in the treatment of anaphylaxis in the view of the new knowledge in the field to support the quality of care and prevention. Recent findings: Some BA, as a single medication or as combined therapy to food or venom immunotherapy, are effectively able to reduce most of the severe anaphylactic reactions. Summary: Anaphylaxis is a recognized clinical emergency, which requires prompt identification and treatment. Several biologic therapies and new devices are emerging as a potential preventive treatment for anaphylaxis. However, adrenaline (epinephrine) is still the first-line treatment for any type of anaphylaxis. Biological drugs, such as omalizumab, whereas not US Food and Drug Administration (FDA) nor European Medicines Agency (EMA) approved for anaphylaxis, have been used as therapeutic adjuvants in the preventive treatment of anaphylaxis, but cost-effectiveness should be considered individually.